2021
DOI: 10.1038/s41598-021-93060-8
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of multi-clade virus-like particle vaccine protects chickens against clade 2.3.2.1 and clade 2.3.4.4 highly pathogenic avian influenza viruses

Abstract: Virus-like particles (VLPs) are recognized as an alternative vaccine platform that provide effective protection against various highly pathogenic avian influenza viruses (HPAIVs). Here, we developed multi-clade VLPs expressing two HAs (a chimera of clade 2.3.2.1c and clade 2.3.4.4c HA) within a single vector. We then compared its protective efficacy with that of a monovalent VLP and evaluated its potency against each homologous strain. Chickens vaccinated with the multi-clade VLP shed less virus and were bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…In addition to generating broad-spectrum VLPs with single HA as vaccine candidate, scientists had also proposed some other strategies for VLP-based vaccine development. Kang et al exploited multi-clade VLPs carrying two HAs derived from two clades, clade 2.3.2.1c and clade 2.3.4.4c, within a single vector, and found that multi-clade VLPs not only show high productivity but also induced effective antibodies [ 14 ]. In contrast to variable surface antigens of HA and NA, the ion channel protein, Matrix protein 2 ectodomain (M2e), represents an alternative antigen target for AVI vaccine, since M2e protein has a relatively conserved sequence and plays a critical role in virus assembly and budding during replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to generating broad-spectrum VLPs with single HA as vaccine candidate, scientists had also proposed some other strategies for VLP-based vaccine development. Kang et al exploited multi-clade VLPs carrying two HAs derived from two clades, clade 2.3.2.1c and clade 2.3.4.4c, within a single vector, and found that multi-clade VLPs not only show high productivity but also induced effective antibodies [ 14 ]. In contrast to variable surface antigens of HA and NA, the ion channel protein, Matrix protein 2 ectodomain (M2e), represents an alternative antigen target for AVI vaccine, since M2e protein has a relatively conserved sequence and plays a critical role in virus assembly and budding during replication.…”
Section: Discussionmentioning
confidence: 99%
“…Since the immune response to CFA, IFA and commercial oil-based adjuvants such as Montanide ISA 70VG, 71VG, 760VG, GEL01, etc., were in a large variation [ 28 ], the use of CFA and IFA might not be able to exactly mimic the clinical situations. We used CFA and IFA for the purpose of evaluating immune response between H5N6-VLPs and H5N6 protein, while ISA 71 VG and Montanide ISA VG70 oil adjuvant might be a better choice to compare the results with others [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, VLP vaccines can provide excellent protection against homologous, heterologous, and heterosubtypic virus infections (9,(17)(18)(19), attributing to its strong ability to stimulate a comprehensive immune response, including humoral, mucosal, and cellular immunities (20)(21)(22)(23)(24). Numerous studies have been conducted to generate poultry VLP vaccines and the majority of these studies centered on production of H5 VLP in various expression systems, including baculovirus (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), silkworm pupae (38,39), and mammalian 293T cells (40), for chicken or duck use. In addition, VLP candidates against other subtypes, such as the H6 and H7 subtypes, were also generated for chicken vaccination, including plant expression system for H6 VLP (41,42), chicken H7 VLP generated from baculovirus (43), and silkworm pupae (44), as well as Escherichia coli (45).…”
Section: Introductionmentioning
confidence: 99%
“…Virus-like particles (VLPs) are highly immunogenic vaccine platforms and efficacies forms of VLP-based vaccines are actively being investigated against a wide array of infectious diseases, including avian influenza. To date, several studies demonstrated that avian influenza HA-expressing VLP vaccines can induce protection [6][7][8][9]. Neuraminidase (NA) is another glycoprotein expressed on the surface of influenza viruses and a strong correlation between the NA antigen and protection can be drawn [10].…”
Section: Introductionmentioning
confidence: 99%